THE IMPROVING OF THE CONTENT OF PROFESSIONALLY ORIENTED TEACHING THE GERMAN LANGUAGE OF THE STUDENTS WHO ARE NOT LINGUISTS - Nataliya Lenyuk (Ternopil Volodymyr Hnatiuk National Pedagogical University, 2016)
In the given article there has been raised the problem of the analysis and selection of the optimum components of the system of professionally oriented teaching a foreign language in a non-linguistic educational establishment. This article discusses the components of system of training professionally oriented foreign language through the content of professional activity. There has been suggested the purpose of teaching a foreign language in a non-linguistic educational establishment as well as the skills the formation of which ensures the achievement of this goal. The subject matter of teaching the German language of the students who are not linguists has been grounded.